Cytoplasmic LIF reprograms invasive mode to enhance NPC dissemination through modulating YAP1-FAK/PXN signaling - Shu-Chen Liu (Nature Portfolio, 2018)
Molecular pathways regulating nasopharyngeal carcinoma (NPC) metastasis are unclear. Here they report higher levels of cytoplasmic leukemia inhibitory factor (cLIF) and LIF receptor (LIFR) to correlate with higher metastasis in NPC patients, and show cLIF to promote NPC metastasis and vascular dissemination via the YAP1-FAK/PXN axis.